Observations on the Pink-footed Goose in central Iceland, 1966 - Hardy, D E (Wildfowl, 1967)
Eleven members of a Radley College Expedition spent from 31st July to 5th September 1966 in central Iceland. Until 16th August investigations were confined to the region west of the Hofsjkull, from Gulaugstungur in the north to Hvtrnes in the south. Scattered areas of meadow in this area are used as moulting grounds for non-breeders. Details of food, behaviour and time of moulting of non-breeding birds are given. The use of separate areas by non-breeders undergoing moult may relieve pressure on available food in the breeding area. Observations on the main breeding colony in pjrsrver, which was inaccessible until the middle of August, are compared with those made in 1951 and 1953. A late cold spring had delayed the breeding cycle by about twelve days. Mortality due to predation was considerable during both early and late stages of the fledging period. Faeces, and viscera of fresh corpses, revealed a definite change in the pattern of feeding during August to a diet rich in soluble carbohydrate. Newly-reported localities for breeding Pinkfeet in the area include a large colony on the Jkulfall river which flows south-west from the Hofsjkull and Kerlingarfjll. The arrival and flocking of Pinkfeet in the Asgar area are compared with observations made in 1954.